ANALYTICAL RESEARCH OF FIQHI TEXT ABOUT ACCEPTANCE OF REPENTANCE OF BLASPHEMER - Dr. Khair Muhammad Asif Memon; Hafiz Abdul Aziz Memon (jihat-ul-islam, 2021)
The love for Holy Prophet (PBUH) is the main component of faith in Islam. That is why Holy Prophet (PBUH) is called the reason of creation of the universe. This is the great position of the Holy Prophet (PBUH). So it is necessary for all of us to show our deepest love, and respect for such a towering figure. We should never indulge into any saying which may cause disobedience to Holy Prophet (PBUH). The protection and the safety of Honour of Prophet Muhammad (PBUH) is primary duty of Muslims. Building of Iman depends on the love of Prophet (PBUH). History of Muslim world witness that Muslims perform this duty with heart and soul. We know very well that anti Islam power tries his best to kick out the love of Prophet (PBUH) from the hearts of Muslims and make the Muslims as dead body. This war of Islam and Kufr is continues and will continue till the day of Judgement. Forgiveness and Punishment of blasphemer is differed among the Scholars and Ulma. Everyone have their own Evidences on their opinions. In this research paper is tried to find out the Reason and the point of difference of scholars so Ummah reach to the right path.